(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Computing and computing are all about us, and they’re only going to becoming more popular. Learning to programme is one approach to get a job in the IT field. Choosing a beginner-friendly programming language is a vital decision for a novice on the route to becoming a programmer. If a newbie chooses a complex language when just beginning out in this profession, he or she may quickly lose enthusiasm in the programming field With so numerous coding programs to choose from, it may be tough for a beginner to know where to start. This paper compares Python and Java, two of the most popular, top-ranked, and in demand programming languages. This article provides a quick review of Python and Java, covering its features, applications, benefits, and drawbacks. The two languages are compared based on their syntax and features. The comparison will also consider the ratio of lines of code (LOC), file capacity, and performance. We need to decide which programming is best for a beginning.